High-throughput automated dissolution method applicable for a wide dose range of controlled release pellets. (2nd July 2016) - Petruševska, Marija; Horvat, Matej; Peternel, Luka; Kristan, Katja
Abstract: The aim of the present study was to demonstrate the application of an automated high-throughput (HT) dissolution method as a useful screening tool for characterization of controlled release pellets in the formulation development phase. Five controlled release pellet formulations with drug substances exhibiting high or low solubility were chosen to investigate the correlation of the automated HT dissolution method with the conventional dissolution testing. Overall, excellent correlations ( R 2 > 0.96) between the HT and the conventional dissolution method were obtained. In one case the initial unsatisfactory correlation ( R 2 = 0.84) and poor method agreement (SD = 12.5) was improved by optimizing the HT dissolution method with design of experiment approach. Here in comparison to initial experimental HT dissolution settings, increased amount of pellets (25% of the capsule filling mass), lower temperature (22 °C) and no shaking resulted in significantly better correlation ( R 2 = 0.97) and method agreement (SD = 5.3). These results show that such optimization is valuable for the development of HT dissolution methods. In conclusion, the high correlation of dissolution profiles obtained from the conventional and the automated HT dissolution method combined with low within-sample and measurement system variability, justifies the utilization of the automated HT dissolution method during development phase of controlled release pellets.